Trace Level Quantification of 4-Methyl-1-nitrosopiperazin in Rifampicin Capsules by LC-MS/MS - Tao, Xiaosha; Tian, Ye; Liu, Wan-Hui; Yao, Shangchen; Yin, Lihui (Frontiers in Chemistry, 2022)
Rifampicin is a first-line anti-tuberculosis drug. However, the presence of 1-methyl-4-nitrosopiperazine (MNP), a nitrosamine impurity, was detected by the US FDA in rifampicin capsules manufactured by Sanofi–Aventis in August 2020. Consequently, the development of efficient methods for the detection of MNP is an important objective. In this study, the MNP in rifampicin capsules was detected using LC-MS/MS. A total of 27 batches of sample from nine manufacturers in the Chinese market were tested, with MNP (0.33–2.36 ppm) detected in all samples at levels exceeding the maximum acceptable intake limit of 0.16 ppm initially set by the FDA. However, after weighing the associated benefits and risks, the FDA-approved limit was revised to 5 ppm; hence, all the samples exhibited MNP levels well below the required limit. Furthermore, the results of forced degradation experiments suggest that MNP is formed by the thermal degradation of rifampicin.